Detection of Honey Adulteration by Addition of Glucose via a Microfiber Coupler - Rosol, Ahmad Haziq Aiman; Isa, Naimah Mat; Irawati, Ninik; Rahman, Husna Abdul; Harun, Sulaiman Wadi (American Scientific Publishers, 2017)
Honey adulteration has become more attractive to producers owing to the limited production levels in recent years and the relative high price of honey. Therefore, the need for more effective and accessible methods aiming at detecting honey adulteration has increased. The present research presents a simple and rapid method to detect adulteration in honey falsified by intentional addition of different concentrations of glucose, using a microfiber coupler (MFC). Different percentage ratios of adulterated honey were prepared; namely 1%, 2%, 3%, 4%, 5% and 6%. The sensor was fabricated by flame brushing technique for detection of glucose in adulteration honey. The proposed sensor furnished acceptable results with a sensitivity of 0.9011 μW/%.